Vultures feeding on the dark side: current sanitary regulations may not be enough. Issue 4 (13th December 2022) - FERNÁNDEZ-GÓMEZ, LOLA; CORTÉS-AVIZANDA, AINARA; ARRONDO, ENEKO; GARCÍA-ALFONSO, MARINA; CEBALLOS, OLGA; MONTELÍO, EUGENIO; DONÁZAR, JOSÉ A.
Summary: It is widely acknowledged that the conservation of vultures, a group of birds threatened worldwide, requires the management of safe, high-quality human subsidies, free of potentially harmful toxic compounds. Additionally, in Europe, the supply of livestock carcasses is subject to current sanitary regulations. It is largely unknown how vultures use sources of food of different abundance, predictability, or different legal status and how individual features shape these preferences. To answer these questions, we took advantage of information yielded by 35 GPS-tagged adult Eurasian Griffon Vultures Gyps fulvus living in a region of northern Spain, which hosts one of the most important European populations. Our results indicated that vultures preferably used predictable feeding sites, such as carcass dumping sites, intensive farms and landfills which together account for the 62% of the observed feeding sites. Less than 10% of all observed sites had permission of authorities for the disposal of the carcasses. Interestingly, sites with large accumulations of carcasses were less used that those with intermediate amounts of food probably because of high intraspecific competition. In addition, sex and breeding status also played a role with males and breeding birds being more prone to visit the studied intensively managed feeding places. This vulture population is heavily dependent on food sources which are not under legal control where the birds could be at risk of intoxication and pathogen acquisition. Hence, current legal scenario allowing farmers to abandon carcasses in their exploitations seems insufficient. The future of vultures in highly anthropized regions is uncertain if interdictory regulations on the abandonment of carcasses of intensive livestock are applied. Additionally, conservation scenarios based on food subsidization must consider the effects of environmental and individual variability. We need science-based strategies ensuring the long-term viability of avian scavenger populations within a scenario of anthropized landscapes and livestock farming intensification.